Response of Lead Fluoride (PbF2) Crystal under X-ray and Gamma Ray Radiation - Vasileios Ntoupis; Dionysios Linardatos; George Saatsakis; Nektarios Kalyvas; Athanasios Bakas; George Fountos; Ioannis Kandarakis; Christos Michail; Ioannis Valais (Photonics, 2023)
Background: In this research, the response of a 10 × 10 × 10 mm3 commercially available PbF2 crystal was experimentally assessed under X-ray and gamma ray radiation to verify the possible application of this material in X-ray medical imaging. Methods: The measurements were performed under X-ray from 50 to 130 kVp and gamma ray excitation (Tc-99m 140 keV and I-131 365 keV). The PbF2 response was experimentally assessed by the determination of the absolute luminescence efficiency (AE), X-ray luminescence efficiency (XLE), and the stopping power of this scintillating crystal in terms of the energy absorption efficiency (EAE). The results were compared with bismuth germanate (BGO) crystal, which is commonly used in medical imaging modalities. Results: The AE of PbF2 gradually decreased from 50 kVp up to 130 kVp. The maximum value was 0.61 efficiency units (EU) at 140 keV, and the minimum value was 0.03 EU at 71 keV (130 kVp). Similarly, low values appeared for the XLE, where the maximum value was 16.9 × 10−5 at 140 keV. Conclusions: These findings show that the PbF2 scintillator has unacceptably low luminescence efficiency. Although PbF2 can effectively absorb radiation, the scintillation light, at room temperatures, is negligible, and, thus, it could not be used in medical imaging applications in the examined energy range.